2020
DOI: 10.1002/hpm.3061
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the inappropriate use of antibiotics in the Rupandehi district of Nepal

Abstract: Introduction: Antimicrobial resistance is a global public health crisis. A major driver of resistance is inappropriate antibiotic use, resulting from practices of prescribers, dispensers and patients. The purpose of this study was to identify the perception of service providers and policymakers about the inappropriate use of antibiotics in Nepal. Methods: A qualitative study was conducted to explore factors influencing antibiotic use. Participants included 17 service providers and policymakers from the Rupande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 63 publications
4
42
0
Order By: Relevance
“…Patients’ pressure also plays crucial role in the prescription and use of antibiotics which may be well reflected in the primary health centers where treatment options are limited and drugs are easily available OTC 10 . In such geographically remote regions, there is a good relationship between healthcare providers and community members, which creates pressure in prescription and sell of the antibiotics asked by patients rather than the appropriate ones 10 , 79 81 . Although policy guidelines demand for use of antibiotics based on the identification of causative agents, in practice, the empirical and over the counter use of antibiotics are high 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients’ pressure also plays crucial role in the prescription and use of antibiotics which may be well reflected in the primary health centers where treatment options are limited and drugs are easily available OTC 10 . In such geographically remote regions, there is a good relationship between healthcare providers and community members, which creates pressure in prescription and sell of the antibiotics asked by patients rather than the appropriate ones 10 , 79 81 . Although policy guidelines demand for use of antibiotics based on the identification of causative agents, in practice, the empirical and over the counter use of antibiotics are high 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported that 90% of dentist prescribe amoxicillin for endodontic infections in Turkey. A number of factors like personal factors (self‐medication and patient pressure to prescribe antibiotics), organizational factors (limited access to laboratory and limited availability of antibiotics in rural areas), and regulatory factors (no monitoring system and restriction to sell/prescribe antibiotics) are responsible for huge and inappropriate use of antibiotics (Nepal et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…4 These bacteria can quickly evolve into antibiotic-resistant strains due to inappropriate antibiotic administration. 5 S. aureus that is resistant to beta-lactam antibiotics is referred to as methicillin-resistant S. aureus (MRSA). 6 In previous studies, it was reported that the presence of MRSA can cause new health problems for humans and animals.…”
Section: Introductionmentioning
confidence: 99%